Spatiotemporal dynamics and drivers of Rift Valley fever outbreaks in Madagascar: A systematic review - Félix Alain; Botovola Miraimila; Zina Antonio Randriananahirana; Sedera Radoniaina Rakotondrasoa; Diana Ratsiambakaina; Fidiniaina Mamy Randriatsarafara; Lantonirina Ravaoarisoa; Radonirina Lazasoa Andrianasolo; Julio Rakotonirina (Journal of Interventional Epidemiology and Public Health, 2026)
Introduction: Rift Valley fever (RVF) is a reemerging viral zoonosis in Madagascar that causes significant economic losses to the livestock sector. Outbreak occurrence and spread are influenced by a complex interplay of environmental variables and animal trading channels. This study examined the spatiotemporal dynamics of RVF outbreaks across the island to guide surveillance and control strategies. Methods: A systematic review was conducted following PRISMA guidelines, encompassing literature published in English or French from 1979 to 2026. Major databases, including PubMed, Google Scholar, and Science Direct, were queried using search algorithms focused on RVF, Madagascar, and spatiotemporal patterns. Results: Twenty-four studies were included in the final analysis. Since the first reported case in 1979, three major epidemic waves occurred in 1990–1991, 2008–2009, and 2021. The East Coast, Central Highlands, Northwest, and Southwest regions were identified as high-risk zones. Outbreaks peaked between January and April, coinciding with the rainy season. While climatic factors trigger initial transmission, the synthesised evidence suggests that livestock movement along trade corridors is a key anthropogenic factor in viral propagation, although the relative contribution of this driver requires further quantitative validation. Conclusion: Rift Valley fever (RVF) dynamics in Madagascar are uniquely determined by regional environmental conditions and human activities. These findings underscore the urgent need for region-specific surveillance and the implementation of an integrated “One Health” approach for effective outbreak management.